Fragment reattachment after atypical crown fracture in maxillary central incisor - Vaz, Vanessa Torraca Peraro [UNESP]; Presoto, Cristina Dupim [UNESP]; Jordão, Keren Cristina Fagundes [UNESP]; Paleari, André Gustavo [UNESP]; Dantas, Andrea Abi-Rached [UNESP]; Segalla, José Claudio Martins [UNESP]; Oliveira Junior, Osmir Batista de [UNESP] (Hindawi, 2014)
Background. Fracture by trauma is one of the most common types of dental injury in the permanent dentition among children and teenagers. Aim. The aim of this study was to report the treatment performed to an atypical dental trauma case in a maxillary central incisor of a young patient by means of reattachment of the tooth fragment. Case Description. A 12-year-old male patient suffered a vertical crown fracture to the maxillary right central incisor. After clinical and radiographic examinations, a conservative restorative treatment which consisted in the reattachment of the tooth fragment with flow resin was performed in order to preserve the dental element and to obtain maximum aesthetics. Conclusion. The reattachment of fractured fragment is a fast and easy technique that can be used successfully as an option to restore dental element which suffered trauma. Clinical Significance. This technique restores the aesthetics and function of the dental element with minimal discomfort to the patient.